Central banking in the 1990s - asset management and the role of gold (World Gold Council GenevaCH, 1995)
Addresses policy concerns about and responses to the changing role of gold in private and official asset structures and their implications for Central Bank policy in the 1990s, including the management of foreign exchange and gold reserves.
DC